Enhancing the Main Contractor-Subcontractor trusting relationship in the United Arab Emirates: A strategic approach to rebuilding trust in complex construction projects - ISSA, RAMAZ SELMAN (2017)
The oil price drop has significantly affected complex construction projects in the United Arab Emirates. After this crisis, adversarial relationships and trust issues between subcontractors and main contractors have increased, therefore, it has become necessary to rebuild trust between them. This dissertation has developed a framework to effectively rebuilding trust between the subcontractors and main contractors throughout the project life cycle. The purpose of this research is to investigate the subcontractors and main contractors’ relationship in complex projects in order to identify the main trust dimensions that impact their relationship, and to define the main factors that contribute to rebuilding trust (i.e., developing, building, and maintaining trust) between them. Based on Zand’s (1972) interpretations, the researcher argued that trust is considered a gradual and self-reinforcing phenomenon that is not an isolated incident; rather, it is built up throughout a project life cycle or many projects. The researcher found that trust factor has a significant impact on subcontractors and main contractors’ relationship, however, there is minor impact of their relationship on building trust between them, and that early contractor engagement in the initiation and planning stage positively impacts the subcontractors and main contractors’ relationship, and that the higher the level of trust between them, the better the project performance. The research also provides recommendations for subcontractors and main contractors to improve their trusting relationships, in addition to recommendations for further study.